Patient perceptions of surgical telehealth consultations during the COVID 19 pandemic in Australia: Lessons for future implementation. Issue 9 (21st June 2021) - Wiadji, Elvina; Mackenzie, Lisa; Reeder, Patrick; Gani, Jonathan S.; Ahmadi, Sima; Carroll, Rosemary; Smith, Stephen; Frydenberg, Mark; O'Neill, Christine J.
Abstract: Introduction: Prior studies of telehealth report high levels of patient satisfaction, but within carefully selected clinical scenarios. The COVID‐19 pandemic led to telehealth replacing face‐to‐face care for many surgical consultations across a variety of situations. More evidence is needed regarding patient perceptions of telehealth in surgery, in particular, exploring barriers and facilitators associated with its sustained implementation beyond the pandemic. Methods: Survey invitations were emailed to a convenience sample of surgical patients by their surgeon following a telehealth consultation during the COVID‐19 pandemic. Surgeons were recruited from a sample ( n = 683) who completed a survey on telehealth (distributed via email to all Australian Fellows of the Royal Australasian College of Surgeons). Mixed methods analysis was performed of the patient survey data. Results: A total of 1166 consultations were captured: 50% routine reviews, 17% initial appointments and 20% post‐operative reviews. Video‐link was used in 49% of consultations. The majority of patients (94%), were satisfied with the quality of their surgical telehealth consultation and 75% felt it delivered the same level of care as face‐to‐face encounters. Telehealth was convenient to use (96%) and led to cost savings for 60% of patients. When asked about future appointment preferences after the pandemic, 41% indicated they would prefer telehealth (24% video‐link and 17% telephone) over face‐to‐face appointments. There was a perception by patients that telehealth consultation fees should be less than face‐to‐face consultation fees. Conclusion: Patient satisfaction with surgical telehealth consultations is high. Barriers to more widespread implementation include financial, clinical appropriateness, technical and confidentiality concerns. Abstract : Patient perceptions of 1166 Australian surgical telehealth consultations during the COVID‐19 pandemic were captured by this survey. Patient satisfaction with telehealth was high with there is significant demand for its continuation. Barriers to more widespread implementation include financial, clinical appropriateness, technical and confidentiality concerns.